Recommendation for modifying current cytotoxicity testing standards for biodegradable magnesium-based materials. (15th July 2015) - Wang, Jiali; Witte, Frank; Xi, Tingfei; Zheng, Yufeng; Yang, Ke; Yang, Yuansheng; Zhao, Dewei; Meng, Jian; Li, Yangde; Li, Weirong; Chan, Kaiming; Qin, Ling
Graphical abstract: Abstract: As one of the most promising medical metal implants, magnesium (Mg) or its alloys have shown significant advantages over other candidates attributed to not only their excellent biodegradability and suitable mechanical properties but also their osteopromotive effects for bone applications. Prior to approval mandated by the governmental regulatory body, the access to the medical market for Mg-based implants requires a series of testing for assurance of their safety and efficacy via preclinical evaluations and clinical tests including phase 1 and 2 evaluations, and phase 3 of multi-center randomized double blind and placebo-controlled clinical trials. However, as the most widely used protocols for biosafety evaluation of medical devices, current ISO 10993 standards should be carefully reevaluated when directly applying them to predict potential health risks of degradable Mg based biomaterials via cytotoxicity tests due to the huge gap between in vitro and in vivo conditions. Therefore, instead of a direct adoption, modification of current ISO standards for in vitro cytotoxicity test is desirable and justified. The differences in sensitivities of cells to in vitro and in vivo Mg ions and the capability of in vivo circulation system to dilute local degradation products were fully considered to propose modification of current ISO standards. This paper recommended a minimal 6 times to a maximal 10 times dilution of extracts for in vitro cytotoxicity test specified in ISO 10993 part 5 for pure Mg developed as potential orthopedic implants based on literature review and our specifically designed in vitro and in vivo tests presented in the study. Our work may contribute to the progress of biodegradable metals involved translational work.